A new species of Rhinoxenoides (Dactylogyridae) parasitizing Triportheus angulatus (Spix & Agassiz, 1829) (Characiformes) from the Juruá River Basin, Brazil - Chinicz Cohen, Simone (2025)
A new species of Rhinoxenoides was described parasitizing the gill filaments of neotropical triportheid fishes. The new species was described from Triportheus angulatus (Spix & Agassiz, 1829) from the Juruá River, State of Acre, Brazil. Rhinoxenoides cruzeirensis n. sp. resembles Rhinoxenoides horacioschneideri Santos Neto, Costa, Soares & Domingues, 2018, mainly by presenting a coiled male copulatory organ (MCO) with clockwise rings; accessory piece with articulation process extending within the coils to the base of MCO; dorsal anchor with well-developed superficial root, and dorsal bar absent. However, it differs from this by number of the coils of the MCO; accessory piece formed by a straight piece that expands in the middle, where it folds over itself; ventral bar short and robust; dorsal anchor with a well-developed superficial root twice as long as the deep root, with a small wing-shaped extension in the distal portion.